Probing the plasmonic near-field by one- and two-photon excited surface enhanced Raman scattering - Kneipp, Katrin (Beilstein-Institut, 2013)
Strongly enhanced and spatially confined near-fields in the vicinity of plasmonic nanostructures open up exciting new capabilities for photon-driven processes and particularly also for optical spectroscopy. Surface enhanced Raman signatures of single molecules can provide us with important information about the optical near-field. We discuss one- and two-photon excited surface enhanced Raman scattering at the level of single molecules as a tool for probing the plasmonic near-field of silver nanoaggregates. The experiments reveal enhancement factors of local fields in the hottest hot spots of the near-field and their dependence on the photon energy. Also, the number of the hottest spots and their approximate geometrical size are found. Near-field amplitudes in the hottest spots can be enhanced by three orders of magnitudes. Nanoaggregates of 100 nm dimensions provide one hot spot on this highest enhancement level where the enhancement is confined within less than 1nm dimension. The near-field enhancement in the hottest spots increases with decreasing photon energy.